Wright Morris - American Writers 69 : University of Minnesota Pamphlets on American Writers - Howard, Leon (Book collections on Project MUSE., 1968)
Wright Morris - American Writers 69 was first published in 1968. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.